In- house preparation of modified Kleihauer-Betke test reagents for estimation of fetomaternal hemorrhage (Latakia University Journal -Medical Sciences Series, 2024)
Fetomaternal hemorrhage (FMH) refers to the entry of fetal blood into maternal circulation before or during delivery. In addition to its role in diagnosing idiopathic neonatal anemia, estimation of FMH is essential in  the passive prophylaxis  programs of hemolytic disease of the fetus and newborn (HDFN) by the appropriate administration of RhDIg to RhD negative women following delivery of D positive babies, or after exposure to a sensitizing event during pregnancy. The Kleihauer-Betke test (KBT) is still considered one of the most important tests in the detection of fetal red blood cells within the maternal circulation. KBT principle is based on the   the characteristic resistance of fetal hemoglobin (HbF) to acid elution, in contrast to adult hemoglobin (HbA). In this study, we aimed to prepare in –house reagents needed in the KBT  to use them in the detection of fetal hemoglobin and the estimation of FMH ,thus alleviating the need to import the highly expensive kits .The modified Kleihauer-Betke method according to Clayton 1963 was adopted in our study, and the required reagents were prepared according to the method depicted in the American Association of Blood Banks (AABB) Technical Manual. Negative controls and different dilutions of positive controls were prepared to test, i the efficinecy of our locally prepared reagents,. Our experiments were carried out at the Central Haematology Laboratory in Tishreen University Hospital. PH measurements of the regeants were performed at a regular intervals throughout a storage period of 60 days, along with their effieveincy in HbF detection and estimation), and the, and both were shown to be constant. KBT using local reagents showed good accuracy in detecting fetal cells with a little tendency to overestimate FMH. According to our results, we can consider this study as a starting point for the use of this reagent in the investigation of unexplained neonatal anemia, and in conducting larger studies of FMH determination in women, thus helping to improve and standardize RhDIg administration.